2017
DOI: 10.3390/bs7010014
|View full text |Cite
|
Sign up to set email alerts
|

Through the Kinesthetic Lens: Observation of Social Attunement in Autism Spectrum Disorders

Abstract: This paper will present a movement-informed perspective to social attunement in Autism Spectrum Disorders (ASD). Background: Dance movement therapy (DMT) is a psychotherapeutic intervention that is used with participants with ASD in various settings. Regular clinical outcome monitoring in an outpatient setting in the Netherlands had shown positive effects on social attunement capacities in young people with ASD. However, a systematic study of the development of social attunement movement behaviors of participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…In DMT, the therapist uses LMA to observe and attend to the client’s movement to change and expand movement components, observe subtle expression of emotion, share these observations with the client, and suggest how to use movement components to foster emotional resiliency in everyday life ( Laban and Ullman, 1980 ; Shafir et al, 2016 ; Tsachor and Shafir, 2017 ). In research, LMA has been used to describe movement associated with diverse topics from personality ( Levy and Duke, 2003 ; Van Koningsveld, 2011 ), mental health issues ( Koch et al, 2007 ; Samaritter and Payne, 2017 ), interpersonal behavior ( Roudposhti et al, 2012 ), emotion and emotional expression ( Lourens et al, 2010 ; Gross et al, 2012 ; Shafir et al, 2016 ), and affect, attitude, and cognition ( Koch, 2014 ; Koch et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In DMT, the therapist uses LMA to observe and attend to the client’s movement to change and expand movement components, observe subtle expression of emotion, share these observations with the client, and suggest how to use movement components to foster emotional resiliency in everyday life ( Laban and Ullman, 1980 ; Shafir et al, 2016 ; Tsachor and Shafir, 2017 ). In research, LMA has been used to describe movement associated with diverse topics from personality ( Levy and Duke, 2003 ; Van Koningsveld, 2011 ), mental health issues ( Koch et al, 2007 ; Samaritter and Payne, 2017 ), interpersonal behavior ( Roudposhti et al, 2012 ), emotion and emotional expression ( Lourens et al, 2010 ; Gross et al, 2012 ; Shafir et al, 2016 ), and affect, attitude, and cognition ( Koch, 2014 ; Koch et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Techniques such as attunement and mirroring, in which a participant leads or follows another's movements or jointly improvises movements with a partner focus on the embodied experience of interactional synchrony, social coordination, and emotional responsivity (Feniger-Schaal et al, 2018). Samaritter and Payne (2017) found that when a dance/movement therapist attuned to (sensed the emotional tone of the actions), and responsively followed, a non-verbal child's movements, the child's own spontaneous interactional behaviors toward the therapist increased. These non-verbal interactional behaviors appeared to follow a development sequence, and when these interactional behaviors are combined, they "contribute to a high complexity of interpersonal engagement and attunement during shared movement actions" (Samaritter and Payne, 2017, pp.…”
Section: Dance/movement Therapymentioning
confidence: 99%
“…Especially, imitative behaviors and synchronized movements are of utmost importance in creating psychological connectedness. Indeed some preliminary studies are now underway that examine how a therapy based on dance (a very basic whole-body rhythmic activity) can help to establish a non-verbal communicative dynamic dyad with a therapist (e.g., Samaritter and Payne, 2017 ).…”
Section: Movement Interventionsmentioning
confidence: 99%